98 Endometrial cancer: the role of prognostic factors and their impact on recurrence pattern. (13th November 2020) - Parpinel, G; Laudani, M; Petronio, N; Peirano, E; Fuso, L; Ribotta, M; Zola, P
Abstract : Introduction: The rate of recurrence of endometrial cancer is 11–19%. It is related to different prognostic factors which define specific risk classes in order to decide for an adjuvant treatment. The objective of this study is to evaluate how prognostic factors influence the probability and pattern of recurrence. Methods: This monocentric observational retrospective study was conducted on 214 patients treated for endometrial cancer between February 2011–2019. The considered parameters were: age, BMI, surgery, stage, LVSI, myometrial infiltration, histological grade, lymph node involvement, adjuvant therapy, relapse. DFS and OS were stratified by the presence or absence of prognostic factors. Results: The rate of recurrence was 18, 7%. DFS was 24, 5 months and OS was 103, 2 months. We observed an increase from 5 to 25% in the distance metastasis rate associated with positive LVSI. The monovariate analysis showed a correlation between DFS and advanced stage (O.R. II 9, 2; III-IV 7, 9 p=0, 0001), positive lymph node infiltration (O.R. 4, 2; p=0, 02), myometrial infiltration (O.R. 4, 3 p=0, 0001) and LVSI (O.R. 2, 4 p=0, 008). A similar result was observed considering the OS and the grading (p=0, 003). We conducted the multivariate analysis of Cox according to the ESGO/ESMO/ESTRO risk class classification and multicollinearity among variables was observed. The results were statistically significant for both DFS (p=0, 002) and OS (p=0, 000). Conclusions: Almost all the considered prognostic factors influence the presence of recurrence, but the stage is the most impactful factor while LVSI correlates with distance metastasis. The definition of the risk factors must be considered to develop targeted therapeutic pathways.